If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(2x + 1) = 0 Reorder the terms: 5x(1 + 2x) = 0 (1 * 5x + 2x * 5x) = 0 (5x + 10x2) = 0 Solving 5x + 10x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x'. 5x(1 + 2x) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {0, -0.5}
| -5(3p+2)-38=3(5p+4) | | 5+1.50=15.50 | | t^4+2t^2+1=0 | | 4.1x-2.6x-8=0.5 | | 3y+-5x=12 | | 2(x)+3(y)=120 | | 4x+-8=-6x+-2 | | 149=7y | | 2x*2+64+8x*2=8x*4 | | 10-8q=2(5-4q) | | 4a+7=5(a+5) | | -(1-3x)=11 | | 3(2+2x)=5(x-5) | | 2(3w-7)=w+11 | | 6(c-2)+9=3+c-6 | | 1.4-0.4x=5.2 | | 2*(7x+2)+12*(x+1)=12 | | 10-x=-13 | | X^2-x+17=0 | | X/2-(x-1/3)=1/9 | | -[10z-(14z+9)]=9+(3z+3) | | 6x-3=91 | | 40-3(2w+1)=11w-3(11+w) | | 3+x=117 | | x^3-2x^2+7x-14=0 | | 66/22r+(16/16-1)=r+(72/3/3) | | tanx=2sinx | | -1(3-4)+1x^2= | | 9s-5q=-4u | | n+9/3=44/9 | | 2+x=120 | | 2(7x+2)+12(x+1)=12 |